The Effects of 5-Hydroxytryptophan in Combination with Different Fatty Acids on Gastrointestinal Functions: A Pilot Experiment - Helene Sauer; Isabelle Mack; Silke Kohler; Stefanie Siegle; Nicole Rieber; Stephan Zipfel; Bärbel Otto; Yvonne Ritze; Stephan C. Bischoff; Paul Enck (Gastroenterology Research and Practice)
Background. Fat affects gastric emptying (GE). 5-Hydroxythryptophan (5-HTP) is involved in central and peripheral satiety mechanisms. Influence of 5-HTP in addition to saturated or monounsaturated fatty acids (FA) on GE and hormone release was investigated. Subjects/Methods. 24 healthy individuals (12f : 12m, 22–29 years, BMI 19–25.7 kg/m²) were tested on 4 days with either 5-HTP + short-chain saturated FA (butter), placebo + butter, 5-HTP + monounsaturated FA (olive oil), or placebo + olive oil in double-blinded randomized order. Two hours after FA/5-HTP or placebo intake, a 13C octanoid acid test was conducted. Cortisol, serotonin, cholecystokinin (CCK), and ghrelin were measured, as were mood and GE. Results. GE was delayed with butter and was normal with olive (P<0.05) but not affected by 5-HTP. 5-HTP supplementation did not affect serotonin levels. Food intake increased plasma CCK (F=6.136; P<0.05) irrespective of the FA. Ghrelin levels significantly decreased with oil/5-HTP (F=9.166; P<0.001). The diurnal cortisol profile was unaffected by FA or 5-HTP, as were ratings of mood, hunger, and stool urgency. Conclusion. Diverse FAs have different effects on GE and secretion of orexigenic and anorexigenic hormones. Supplementation of 5-HTP had no effect on plasma serotonin and central functions. Further studies are needed to explain the complex interplay.